Effect Of Poly-Ethylene-Co-Methyl Acrylate-Coglycidyl Methacrylate - Roslly, Nurul Amira Izzatie (Universiti Sains Malaysia, 2017)
The effect of different compositions of polybutylene terephthalate (PBT) and low density polyethylene (LDPE) blends (20/80, 50/50, 80/20 of PBT/LDPE) and the effect of different amounts (5, 10 and 15 wt%) of poly (ethylene -co- methyl acrylate -co- glycidyl methacrylate) (EMAGMA) terpolymer and polyethylene grafted maleic anhydride (PEg- MA) as compatibilizers on the mechanical and morphological properties of PBT/LDPE blends were investigated. Field emission scanning electron microscope (FESEM) showed two phase morphology with poor interaction between the phases. Based on mechanical properties, 80PBT/20LDPE exhibited the highest tensile strength and modulus and it was considered as the optimum blend system. Incorporation of EMAGMA or PE-g-MA as compatibilizer in the 80PBT/20LDPE blend showed improvement in impact strength but reduction in tensile strength. However, 80PBT/20LDPE blend with EMAGMA have better mechanical properties compared with the blend with PE-g-MA, even though the mechanical properties lowered than uncompatibilized 80PBT/20LDPE blend. FESEM study indicated less phase separation suggesting better interaction between the components in PBT/LDPE/EMAGMA blends compared with the PBT/LDPE/PE-g-MA blends. In conclusion, EMAGMA is considered as a better compatibilizer compared with PE-g-MA, but it could not act as an effective compatibilizer for the PBT/LDPE blend system at low content.